PENGARUH MODEL PEMBELAJARAN TREFFINGER BERBASIS OPEN ENDED PROBLEM TERHADAP BERPIKIR KREATIF SISWA PADA MATERI LARUTAN PENYANGGA - M. Raidil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The results of the interview showed that the level of communication and reasoning of students in the buffer solution subject was quite below average, especially in giving opinions and analyzing different problems. Learning is student-centered which should be teacher-centered. The study was conducted to determine the effect of implementing the Treffinger learning model based on open-ended problems on students' creative thinking on the material of buffer solutions. This study is a quasi-experimental study with Pretest Posttest Nonequivalent Control Group Design, using two classes that were compared. Each class was given an initial and final knowledge test. Essay tests and observation sheets were the instruments used. Data analysis used the t-test, before the t-test was carried out, normality and homogeneity were tested first. In this study, it was proven that there was a significant effect of using the Treffinger model based on Open Ended Problem s on students' creative thinking on the material of buffer solutions as evidenced by the calculated t value> t table.